Perjalanan Emosional dan Psikologis Pelaku UMKM Perempuan dalam Mengelola Usaha Kecil - Asrianto Asrianto; Anwar Ramli; Anwar Rauf; Romansyah Sahabuddin; Masnawaty Sangkala; Samirah Dunakhir (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
Women entrepreneurship in Micro, Small, and Medium Enterprises (MSMEs) plays a vital role in the local economy. However, women entrepreneurs often face complex emotional and psychological challenges due to their dual roles as housewives and entrepreneurs. Market uncertainty, social pressure, and lack of support from their environment further burden their workload. This study aims to explore the subjective experiences of women micro MSMEs, particularly in dealing with the psychological pressures of carrying out these roles. The research method used is a qualitative phenomenological approach with seven informants from the culinary, handicraft, and online trading sectors. Data were collected through semi-structured interviews and non-participant observation, then analyzed using a thematic approach based on the Miles & Huberman model. The results of the study revealed four main themes: (1) the pressure of dual roles that often trigger stress and emotional exhaustion (burnout), (2) chronic anxiety related to fear of business failure and income instability, (3) spirituality and religious activities as meaning-based coping mechanisms, and (4) the importance of social support from partners, family, and community as a balance of emotional conditions. These findings confirm that the success and sustainability of women's businesses depend not only on economic capital or technical skills, but are also significantly influenced by mental health and the strength of social networks. Therefore, empowerment programs for women's MSMEs need to be designed holistically, encompassing psychosocial aspects, coping strategy training, and strengthening supportive and inclusive social networks.